Effect of Adsorbent Dosage on Copper Ion Adsorption Using Activated Carbon of Langsat Shell (Lansium domesticum Corr) with Column Method - M Yogi Yunanda; Desy Kurniawati (Universitas Negeri Medan, 2023)
Copper is one of the dangerous heavy metals contained in industrial wastewater, whose presence needs to be addressed. Adsorption is one method that can be used to adsorb heavy metals. Using a langsat shell as an adsorbent is used to adsorb copper because it is easy to obtain and its use is still minimal in people. Using the column method, the langsat shell was made into activated carbon with HNO3 as an adsorber of Cu2+ metal ions. The activated carbon obtained was tested for quality according to Standard Nasional Indonesia (SNI) No.06-3730-1995. In this research, we determine the effect of adsorbent dosage on the adsorption of copper ions. The results showed the activated carbon meets established quality standards of SNI and the optimum adsorption value of Cu2+ metal ions at an adsorbent dosage of 0.4 grams.